2006
DOI: 10.1080/09595230600741198
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and its correlates in an Australian prisoner population

Abstract: Despite evidence of high rates of smoking among prisoners, there has been limited research that describes smoking patterns and risk factors associated with smoking in this group. This study describes inmate smokers and identifies factors associated with smoking in prison, using a survey comprising a cross-sectional random sample of inmates stratified by sex, age and Aboriginality. A total of 914 adult inmates (747 men, 167 women) were recruited from 29 New South Wales (Australia) correctional centres. Informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
16

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 11 publications
5
33
0
16
Order By: Relevance
“…Approximately 70% -80% of prisoners have been identifi ed as current smokers ( Belcher, Butler, Richmond, Wodak, & Wilhelm, 2006 ;Colsher, Wallace, Loeffelholz, & Sales, 1992 ;Conklin, Lincoln, & Tuthill, 2000 ;Cropsey, Eldridge, & Ladner, 2004 ;Cropsey, Eldridge, Weaver, Villalobos, & Stitzer, 2006 ;Cropsey & Kristeller, 2003, 2005Sieminska, Jassem, & Konopa, 2006 ). Consistent with previous population data, one study with female prisoners found prevalence rates of smoking to be higher for Whites than Blacks (79.5% vs. 71.3%; Cropsey et al, 2004 ) and found that Black female prisoners smoked fewer cigarettes per day than did White prisoners (11.1% vs. 19.2%;Cropsey et al, 2006 ).…”
Section: Original Investigationsupporting
confidence: 74%
“…Approximately 70% -80% of prisoners have been identifi ed as current smokers ( Belcher, Butler, Richmond, Wodak, & Wilhelm, 2006 ;Colsher, Wallace, Loeffelholz, & Sales, 1992 ;Conklin, Lincoln, & Tuthill, 2000 ;Cropsey, Eldridge, & Ladner, 2004 ;Cropsey, Eldridge, Weaver, Villalobos, & Stitzer, 2006 ;Cropsey & Kristeller, 2003, 2005Sieminska, Jassem, & Konopa, 2006 ). Consistent with previous population data, one study with female prisoners found prevalence rates of smoking to be higher for Whites than Blacks (79.5% vs. 71.3%; Cropsey et al, 2004 ) and found that Black female prisoners smoked fewer cigarettes per day than did White prisoners (11.1% vs. 19.2%;Cropsey et al, 2006 ).…”
Section: Original Investigationsupporting
confidence: 74%
“…Almost the same and higher rates of smokers have been reported in other Greek and international surveys [33,34,36,38,[72][73][74][75][76][77]. According to the study results, women increased their smoking habits by 20.8% during their detention period, while in previous surveys conducted in two Greek male prisons the relevant increase rates were higher (37.7% and 43.4% respectively) [33,34].…”
Section: Discussionmentioning
confidence: 39%
“…71%, N= 5959, Bereich zwischen 48% und 97% (Awofeso 2000) 72% (Awofeso, Irwin et al 2008) 78%, N= 747 (Belcher, Butler et al 2006) NSW 2001: 90%; 1996: 88% (Butler, Richmond et al 2007) 87% N=446 (Holmwood, Marriott et al 2008) 77% und 83%, verglichen mit 17.4% in der allgemeinen Gesellschaft (Richmond, Butler et al 2006) Ein Unterschied in der Prävalenz zwischen Städtischen Gefängnissen (77%) und nicht städtischen Gefängnissen (69%) wurde beschrieben (p<0.001) (Awofeso 2000).…”
Section: Literaturstudieunclassified
“…81%, N= 5959 (Awofeso 2000) 83%, N= 167 (Belcher, Butler et al 2006) 88%, N=72 (Holmwood, Marriott et al 2008) 82.9% der weiblichen Gefangenen, die an einer Gesundheitsumfrage teilnahmen (Queensland, N=212) waren Raucherinnen (Young, Waters et al 2005 70.6% Lebenszeitprävalenz, 46.6% tägliche RaucherInnen, N= 4381 (Cropsey, Linker et al 2008) Australien Die Vergleichsdaten für Raucher in der Allgemeinbevölkerung sind wie folgt:…”
Section: Kanadaunclassified
See 1 more Smart Citation